Modelling the food web for assessment of the impact of stock supplementation in a reservoir ecosystem in India. (October 2015) - Khan, M. F.; Preetha, P.; Sharma, A. P.
Abstract Comparative estimates of trophic status and energy flow were carried out in a tropical reservoir ecosystem in India to assess the impact of fish stocking. Mass‐balanced models of the reservoir ecosystem were constructed for two periods – 1982–1983 and 2002–2003 – using ecopath software to determine the impacts on different groups before and after stocking. Mixed trophic impact (MTI) analyses indicated that phytoplankton and detritus have a positive impact on most groups. There was a decrease in nutrient flow through the system from pre‐stocking to post‐stocking (22.28%). The baseline was higher by 0.29% in the post‐stock phase indicating maturity. The ecosystem indices tested indicate that the reservoir was in a more resilient state post‐stocking than during the pre‐stocking phase. The 'health' of the ecosystem showed an improvement, which indicates a positive impact of stocking.